POI05 StayingSmart—an online web resource about cognitive deficits in multiple sclerosis for patients, carers and professionals. Issue 11 (22nd October 2010) - Langdon, D; Russell, N; Field, A; Fox, L
Abstract : Many people with multiple sclerosis (MS) experience cognitive problems. In community samples, about half show reduced performance on standardised cognitive tests and in clinic samples, just over half. Information about cognitive difficulties is not easily accessible. Although there are a few pamphlets and books available, they have to be located by people with MS before they can be obtained and read. The person with MS also has to realise and acknowledge that they have cognitive difficulties. To meet the needs of the Google generation, the web-based tool StayingSmart has been developed. It starts with frequent everyday problems, such as "I lose my keys", which when "clicked" leads the website user through multilayered information which targets the relevant cognitive domain. "Tips and Tricks" lists simple practical strategies to overcome daily difficulties; "Brief Info" and "More Info" summarise how MS affects the particular cognitive domain; "Evidence Base" reviews the scientific evidence; "Gadgets and Gizmos" lists items that may help; "Further Resources" lists relevant books and other publications; there is a section on "Getting Professional Help". There is also a Fast Track stream to allow health professionals to access and print all information in one document. There are links to Facebook and Twitter.